An observational study of hand hygiene compliance in paediatric wards. Issue 17 (12th June 2012) - Randle, Jacqueline; Firth, Joseph; Vaughan, Natalie
<x xml:space="preserve">Abstract</x> Aims and objectives. To measure healthcare workers', children's and visitors' hand hygiene compliance in a paediatric oncology ward and a paediatric respiratory ward in an English hospital. Background. Children are especially vulnerable to healthcare‐associated infections, yet few studies have reported on hand hygiene compliance in paediatric clinical areas. Design. This was an observational study. Method. We measured hand hygiene compliance over an eight‐hour period in two hospital wards using the 'five moments of hand hygiene' observation tool. We monitored a total of 407 hand hygiene opportunities. Results. Overall opportunities for compliance were 74% for healthcare workers (n = 315) and children and visitors 23% (n = 92). Compliance was 84% for allied health professionals, 81% for doctors, 75% for nurses and 73% for ancillary and other staff. Hand hygiene compliance varied depending on which of the five moments of hygiene healthcare workers were undertaking (p < 0·001), with compliance before child contact 90% (140/155); after child contact 78% (89/114); after body fluid exposure 75% (3/4); and after surroundings contact 36% (15/42). For healthcare workers and visitors, there was no evidence of an association between time of day and their hand hygiene compliance, and for visitors to the oncology ward, hand hygiene compliance was higher (p < 0·05). Conclusion. Owing to the nature of the clinical environments, we are unable to draw conclusions about children's hand hygiene compliance; however, visitors' compliance was low. Among healthcare workers, levels of compliance were higher compared with previous reported estimates. Relevance to clinical practice. Visitors had the lowest level of compliance yet owing to the nature of the clinical environments, nearly a quarter of care is delivered by them rather than healthcare workers, and so, this offers opportunities for specific future interventions aimed at families and carers.